2021
DOI: 10.1099/ijsem.0.005157
|View full text |Cite
|
Sign up to set email alerts
|

Micromonospora humida sp. nov., exhibiting antimicrobial potential, isolated from riverside soil

Abstract: An actinobacterial strain designated MMS20-R1-14T was isolated from a riverside soil sample. Colonies on agar plates were orange to strong orange brown in colour, which later became black. The cells grew at 10–40 °C (optimum, 37 °C), pH 5.0–11.0 (pH 8.0) and in the presence of 0–4 % NaCl (1 %). The 16S rRNA gene sequence of strain MMS20-R1-14T showed highest similarities to Micromonospora wenchangensis CCTCC AA 2012002T (99… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…All strains were negative in tests for nitrate reduction, indole production, glucose fermentation, α-chymotrypsin, N-acetyl-β-glucosaminidase, α-mannosidase and α-fucosidase, assimilation of mannitol, N-acetyl glucosamine, capric acid, adipic acid, malic acid, citrate and phenylacetate, and hydrolysis of hypoxanthine and tyrosine. Data for growth ranges and polar lipids of compared species were taken from original studies [34][35][36][37][38], and DNA G+C contents were from the GenBank Microbial Genomes database (www.ncbi.nlm.nih.gov/genome/microbes/). All other data were obtained from this study.…”
Section: Genome Featuresmentioning
confidence: 99%
“…All strains were negative in tests for nitrate reduction, indole production, glucose fermentation, α-chymotrypsin, N-acetyl-β-glucosaminidase, α-mannosidase and α-fucosidase, assimilation of mannitol, N-acetyl glucosamine, capric acid, adipic acid, malic acid, citrate and phenylacetate, and hydrolysis of hypoxanthine and tyrosine. Data for growth ranges and polar lipids of compared species were taken from original studies [34][35][36][37][38], and DNA G+C contents were from the GenBank Microbial Genomes database (www.ncbi.nlm.nih.gov/genome/microbes/). All other data were obtained from this study.…”
Section: Genome Featuresmentioning
confidence: 99%
“…Riverside soil environment harbours high bacterial diversity, from which a number of novel bacterial taxa have been reported recently [5–7]. In this study, a novel actinobacterial strain capable of degrading a wide range of substrates was isolated from riverside soil, and a new species of Nocardioides is proposed based on the polyphasic taxonomic characterization.…”
Section: Introductionmentioning
confidence: 98%
“…Generally, phenotypic comparison of Brevibacillus is not straightforward, as most strains show poor activities in biochemical and physiological tests [6,7]. Through a series of recent studies, riverside soil has been found to be a unique environment and also a rich source of microbial diversity [8][9][10]. In this study, a novel strain designated MMS20-4M-10-Y T was isolated from riverside soil.…”
Section: Introductionmentioning
confidence: 99%
“…Through a series of recent studies, riverside soil has been found to be a unique environment and also a rich source of microbial diversity [8–10]. In this study, a novel strain designated MMS20-4M-10-Y T was isolated from riverside soil.…”
Section: Introductionmentioning
confidence: 99%